ANALYSIS OF THE POTENTIAL USE OF ARTIFICIAL INTELLIGENCE, DIVISION OF JOB DESKS AND TEAM COMMUNICATION ON EMPLOYEE PERFORMANCE AT PT. MINA BERKAH SELALU - Mochammad Azharuddin Haidi; Kumara Adji; Sumartik; Khoong Tai Wai (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to find out and measure how much influence the potential use of Artificial Intelligence, job desk division and team communication on employee performance at PT. Mina Berkah Selalu. Method: This research includes quantitative research using an explanatory research approach. The population in this study is taken from the number of all employees at PT. Mina Berkah Selalu. The sample obtained amounted to 50 respondents with a total sampling data collection technique. Data collection in this study was by observation and distribution of questionnaires measured using the Likert scale. This study uses the Structural Equation Modeling (SEM) analysis method. The data analysis technique used in this study uses PLS (Partial Least Square) version 4.0. Results: The results of this study show that the use of Artificial Intelligence and the division of jobdesks have a positive and significant influence on employee performance. However, team communication has no effect and is not significant to employee performance. Novelty: This study provides empirical evidence on how the integration of Artificial Intelligence and organizational structure (job desk division) can enhance employee performance in a corporate environment, while also identifying that team communication may not always directly impact performance outcomes.